2003
DOI: 10.1038/sj.npp.1300296
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone (CRH) mRNA Expression in Rat Central Amygdala in Cannabinoid Tolerance and Withdrawal: Evidence for an Allostatic Shift?

Abstract: Chronic treatment with cannabinoid agonists leads to tolerance. One possible mechanism for this is receptor internalization, but tolerance has also been reported with compounds that only cause internalization to a low degree. Furthermore, cannabinoid antagonist administration precipitates a characteristic withdrawal syndrome in tolerant subjects, accompanied by neuronal activation and enhanced release of corticotropin-releasing hormone (CRH) in the central amygdala. The underlying molecular mechanisms are unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The observed anxiogenic effects of cannabinoids agree with previous results in the emergence and EPM tests (Rodriguez de Fonseca et al, 1996;Arevalo et al, 2001;Caberlotto et al, 2004;Marco et al, 2004) and the social interaction test (Genn et al, 2004). Adolescent behavior in rodents is characterized by greater social interaction and exploratory behavior relative to adults (Spear, 2000) and such effects were evident in control rats in the social interaction and EPM tasks in the present study.…”
Section: Acute Anxiogenic Effects Of Thcsupporting
confidence: 93%
“…The observed anxiogenic effects of cannabinoids agree with previous results in the emergence and EPM tests (Rodriguez de Fonseca et al, 1996;Arevalo et al, 2001;Caberlotto et al, 2004;Marco et al, 2004) and the social interaction test (Genn et al, 2004). Adolescent behavior in rodents is characterized by greater social interaction and exploratory behavior relative to adults (Spear, 2000) and such effects were evident in control rats in the social interaction and EPM tasks in the present study.…”
Section: Acute Anxiogenic Effects Of Thcsupporting
confidence: 93%
“…Previous studies suggest that tolerance to the behavioural effects of HU210 develops after repeated chronic or subchronic administration of the drug [5,9,11,16,18,40]. It has been suggested that the development of behavioural tolerance to cannabinoids such as THC, CP55,940 and WIN55,212-2 is mainly a pharmacodynamic event and can be correlated with a downregulation and desensitization of CB1 receptors in the brain [18,28,57].…”
Section: Cb1 Binding Decrease Correlates With Body Weight Lossmentioning
confidence: 99%
“…Studies involving other cannabinoids such as THC, CP55,940 and WIN55,212-2 have shown that the development of behavioural drug tolerance is mainly a pharmacodynamic event and can be correlated with a downregulation and desensitization of CB1 receptors in the brain [18,28,57]. Although Caberlotto et al [5] described a downregulation in CB1 mRNA expression in the striatum only after chronic HU210 administration, the regional effects of HU210 treatment on CB1 receptor density in the rat brain is yet to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Rimonabant, an antiobesity drug, increases CRH levels 84 while decreasing ACTH and cortisol at low doses, but increases both at high doses. 85 Traditional antidepressants such as fluoxetine, citalopram and imipramine all decrease CRH, ACTH and cortisol levels.…”
Section: A B C D E F G Hmentioning
confidence: 99%